Different Multilayer Substrate Approaches to Improve Array Antenna Characteristics for Radar Applications - N. Chater; T. Mazri; M. Benbrahim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The aim of this paper is to investigate deeply in multi-layer substrate technique as a way of improving the characteristics of patch array antenna for electronic scanning radar application. The basic array antenna consists of 8 patches mounted on a FR-4 substrate and operating at 3GHz frequency. The feeding technique is microstrip technology. This structure has some disadvantages as a poor gain and a narrow bandwidth. In fact, the obtained gain value does not exceed 7 dB which could be explained by the lossy nature of the FR4 substrate. On the other side, the narrow bandwidth is caused by the microstrip limitations. For this reason, the technique of multi-layer substrate is proposed in this paper. Many approaches are investigated and the distance between the layers is studied. The design and simulations of each approach are performed under the tool Advanced Design System of Keysight Company. A comparison between simulation results of all approaches including simulation results of the basic array antenna will be analyzed.